Lenny Krayzelburg at 185 m of His Winning 200 m Backstroke Race at the 1998 Goodwill Games in New York - Rushall, B. S. (1999)
Video pictures (14 frames) and the appropriate technical/ biomechanical explanations for Lenny Krayzelberg at 185 m of His Winning 200 m Backstroke Race at the 1998 Goodwill Games in New York.